2018
DOI: 10.1136/bmj.k3218
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with requirement to report results on the EU Clinical Trials Register: cohort study and web resource

Abstract: ObjectivesTo ascertain compliance rates with the European Commission’s requirement that all trials on the EU Clinical Trials Register (EUCTR) post results to the registry within 12 months of completion (final compliance date 21 December 2016); to identify features associated with non-compliance; to rank sponsors by compliance; and to build a tool for live ongoing audit of compliance.DesignRetrospective cohort study.SettingEUCTR.Participants7274 of 11 531 trials listed as completed on EUCTR and where results co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
151
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(166 citation statements)
references
References 16 publications
13
151
0
2
Order By: Relevance
“…Legal regulations concerning dissemination of clinical trial results are similar in the EU and the USA. In general, there is a requirement both to prospectively register and to post basic information including summary results of clinical trials on a clinical trial register (EU Clinical Trial Register [EUCTR] and ClinicalTrials.gov for the EU and the USA, respectively) . The data about clinical trials contained in those registers are publicly available on the respective websites .…”
Section: Legal Regulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Legal regulations concerning dissemination of clinical trial results are similar in the EU and the USA. In general, there is a requirement both to prospectively register and to post basic information including summary results of clinical trials on a clinical trial register (EU Clinical Trial Register [EUCTR] and ClinicalTrials.gov for the EU and the USA, respectively) . The data about clinical trials contained in those registers are publicly available on the respective websites .…”
Section: Legal Regulationsmentioning
confidence: 99%
“…Studies with a noncommercial sponsor were substantially less likely to post results compared with those with a commercial sponsor. Moreover, the study revealed numerous errors, omissions and contradictory entries in EUCTR . So far, this has been the only study to evaluate the compliance with the Guideline 2012/C 302/03.…”
Section: Legal Regulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on non-reporting of trial results came from evidence published in The BMJ this year by Ben Goldacre and colleagues at the Evidence-Based Medicine DataLab at the University of Oxford’s Nuffield Department of Primary Care Health Sciences 2. They identified 7274 trials where results were now due and found that only 49.5% had reported.…”
mentioning
confidence: 99%